Analisis kata Ad-Dakhil dan Al-Muarrob dalam teks berita Arab Al Jazeera - Salsabila, Eva Laily (Maliki Interdisciplinary Journal, 2024)
Ad-dakhil is It is all that entered the Arabic language in the form of foreign vocabulary in the various periods from its appearance to the present, whether it is used by Fashih Arabs or those who are not Arabian. While Al-Muarrob is the transfer of a foreign language into Arabic or ranslate into Arabic, Al-Muarrab means something that is made as Arabic. The purpose of writing this article are : (1) To know the science of Ad-Dakhil dan Al-Muarrob from the perspective of the experts. (2) To know to know and analyze the difference between the two of Ad-Dakhil and Al-Muarrob and the factor both of them. (3) knowing the results of research in the field of Ad-Dakhil and Al-Muarrob science in Al Jazeera Arabic News Text. The results of the study proved that There are several words ad dakhil and al muarrob present in the Arabic news text of Al Jazeera and also explained the differences between the two.